2016
DOI: 10.1088/0031-8949/91/11/115603
|View full text |Cite
|
Sign up to set email alerts
|

On the formation process of charged clusters

Abstract: The clustering process of charged grains often resembles a formation stage of colloidal and spongy matter, as well as some astrophysical objects. In this paper, molecular dynamics simulation is used to simulate the formation process of clusters of massive charged grains in plasmas. It is found that, from an initially uniform distribution of grains with Maxwellian velocity distribution, a statistically stationary system of clusters, each with different dynamic as well as thermodynamic characteristics, can form.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The differences among the models lie in the ranges and magnitudes of the two regimes. In our simulation, the grain-grain interaction is governed by a modified-Yukawa potential [19,20,[28][29][30][31]33] U int (r i j ) = q 2 r i j exp − r i j…”
Section: Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences among the models lie in the ranges and magnitudes of the two regimes. In our simulation, the grain-grain interaction is governed by a modified-Yukawa potential [19,20,[28][29][30][31]33] U int (r i j ) = q 2 r i j exp − r i j…”
Section: Formulationmentioning
confidence: 99%
“…[3,4,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Recently it has been shown that by tailoring the external force one can obtain controllable compact structures such as dust-grain crystals, [26,27] and the time required to reach the cluster state decreases with external force increasing. [28][29][30][31][32][33] Although what happens after the external force has been withdrawn can be important in many applications, [1] it has not been investigated. In this paper, we use molecular dynamics (MD) simulation to investigate the evolution of charged grains in a 2D dusty plasma under an external force, particularly the long-time evolution of the resulting grain crystal after it has been withdrawn.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, dusty plasmas have attracted much research attention because they play important roles in many phenomena in the astrophysical environments, the Earth's ionosphere, 2–7 as well as in industrial processes such as semiconductor device manufacturing, plasma etching, materials coating and modification, etc 1,6–9 . As a result, there has been much interest in the theory and applications of dusty plasmas, covering a large range of the physical parameters involved 10–35 . Since the electrons have much higher mobility, inelastic collisions between the electrons and dust grains are much more frequent than that of ions, so that the dust grains are usually highly negatively charged 10 …”
Section: Introductionmentioning
confidence: 99%
“…Song et al 22 studied the effect of the plasma temperature on the structures and the dynamics of dust clusters, and found that depending on the discharge power, dust clusters can also be in crystal or liquid states. Existing studies have also considered various internal and external, such as ion and neutral‐particle drag, thermophoretic, radiation pressure, gravitational, etc., forces and other effects on the dynamics and structure of dust grains in a plasma 11–35 …”
Section: Introductionmentioning
confidence: 99%